Needs, Motivations, and Abilities: Exploring the Perspectives of Science High School Educators in Performing and Writing Research - Galdonez, Dominic Patric (International Journal of Research in STEM Education, 2023)
Education is a constantly evolving field, driven by the increasing demand for innovative teaching methods. Teachers, often seen as the cornerstone of education, assume a multifaceted role that extends beyond the classroom. They actively engage in educational research, contributing significantly to the advancement of teaching and learning. This study aimed to collect, analyze, and comprehend the perceptions of teachers at the Philippine Science High School-Ilocos Region Campus in conducting and writing meaningful research. Utilizing a quantitative research approach, the study includes twenty-five (25) teachers from the Philippine Science High School-Ilocos Region Campus as respondents. A researcher-developed survey questionnaire, designed based on existing literature, serves as the primary data collection tool. Key findings from this research reveal that: teachers tend to hold a relatively negative perception of research-related factors within their school environment; teachers maintain a positive stance toward research in their professional roles; teachers are intrinsically motivated by research in their professional development; teachers recognize the presence of research-related difficulties within their professional roles; teachers exhibit a strong aptitude for planning research-related activities; teachers demonstrate impressive writing skills in the context of research. In summary, this study sheds light on the perceptions and experiences of teachers engaged in research activities at the Philippine Science High School-Ilocos Region Campus. It highlights the nuanced dynamics of their involvement, from mixed perceptions of research support to their unwavering motivation and commendable skills in planning and writing research papers. This research provides valuable insights for educators and institutions seeking to enhance research engagement and productivity among their teaching staff.